Thymoma Profile at Dr. Moewardi General Hospital: Does Thymoma Size Really Affect Distant Metastasis? - Thomas, Novita Silvana; Fahlevie, Fahlevie; Setijadi, Ana Rima; Widiastuti, Widiastuti; Rakhma, Sastia (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Size is a predictor factor of a patient's prognosis and metastasis in solid tumors. This study determined the relationship between thymoma size and distant metastasis. Methods: A cohort retrospective study using medical record data was conducted at Dr. Moewardi General Hospital, Surakarta, from January 2019 to August 2021. Of 1,430 thoracic oncology patients, 150 (10%) had mediastinal mass with thymoma as the majority (48.6%). About 73 thymoma patients were included. The size of the thymoma was the dependent variable, and the metastasis (distant and non-distant) was the independent variable. The cut-off point of thymoma size was determined with receiver operating characteristic (ROC) analysis. The correlation of thymoma size with distant metastasis was analyzed with the Chi-Square test, and p < 0.05 was considered significant. Results: Thymoma was predominated by males (53.4%), the mean age was 43 ± 16 years old, and dyspnea was the most common symptom. Metastatic lesions were found in 87.7% of the patients, and the most common metastatic sites were intrathoracic (79.5%), followed by axillary lymph nodes (49.3%), bone (21.9%), liver (20.5%), and brain (1.4%). The cut-off value of thymoma size was 8.25 cm, indicating that >8.25 cm was categorized as large thymoma. Distant metastasis was found in 86.0% of large thymoma patients. The large tumors tend to spread into various sites (OR = 5.39; 95% CI 2.8-32.6; p = 0.002). Conclusion: Thymoma must be taken into account when there are male patients in their forties presented with dyspnea and mediastinal mass. The cut-off point of 8.25 cm for the thymoma size can predict distant metastasis.